The Effectiveness of Using Interactive Learning Media Based on the Google Sites Website on Dynamic Electricity Material - Yusnidah Yusnidah; M Iman Hidayat; Dodi Maulana (Jurnal Sinestesia, 2023)
The purpose of this study to provide an overview of the understanding of physics concepts in dynamic electricity material for XII IPA students of Darul Ulum IT High School Padang Sidempuan, North Sumatra Province before and after using the google site in the learning process. Sampling was carried out by purposive sampling, the instrument used was a concept understanding test, observation and student response questionnaires. Quantitative analysis techniques are used to measure the level of understanding of students. The results showed that there were differences in understanding the physics concept of dynamic electricity before the application of the google site with an average value of 40.5 and after the application of the google site with an average value of 51. So it can be concluded that the hypothesis is accepted in achieving increased understanding of dynamic electricity material physics concepts in class XII Darul Ulum IT High School.